STRESS AND COPING AMONG PARENTS WITH CHILDREN ENROLLED IN REMOTE SCHOOLING DURING COVID-19 - Chevalier, Jocy-Anna; Andrews Adlam, Johanna; Thompson-Robinson, Melva; Dodge Francis, Carolee; Anderson, Eboni; Traylor, Daryl O. (International Journal of Child, Youth and Family Studies, 2024)
The COVID-19 pandemic necessitated the closure of schools, prompting 93% of U.S. households with children to transition to remote schooling. This study investigates coping mechanisms used by parents and the emotional impact of remote schooling on their well-being. A cross-sectional online survey, grounded in the Transactional Model of Stress and Coping, was conducted among 133 U.S. parents with children engaged in remote schooling from May to October 2020. Pearson correlations and paired sample t-tests were calculated. Multiple regression was performed to determine how well stress, resilience, and gender predict depressive symptoms. The study participants had an average of 1.96 children. Most commonly used coping mechanisms included planful problem-solving, seeking social support, and escape/avoidance. A statistically significant positive association was found between stress and depressive symptoms. Stress and depressive symptoms increased during the pandemic, while resilience decreased. The resulting statistically significant regression model of stress, resilience, and gender accounted for 75.4% of the variability in depressive symptoms. These results underscore the importance of addressing parental well-being and mental health during times of crisis, particularly when children are engaged in remote schooling.